2013
DOI: 10.1007/s00383-013-3302-z
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcome analysis of children with traumatic out-of-hospital cardiac arrest compared to nontraumatic cardiac arrest

Abstract: Significant factors related to sustained ROSC have been identified as initial cardiac rhythm, duration of in-hospital CPR, and the period from scene to hospital. Head and neck injuries were the majority of traumatic cases and the prevention in head and neck trauma may play an important part in public health aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 19 publications
1
24
1
Order By: Relevance
“…The finding is consistent with the result from a previous study at our center29 as well as other studies reporting that pediatric patients are at a higher risk for cardiac arrest and higher morbidity in the peri- and postoperative periods in traumatic cases. It was also reported that pediatric patients with high ASA physical status classification suffering from injury before receiving anesthesia had a higher cardiac arrest and comorbidity rate 13,11,18,30. Several factors may explain this increased risk of cardiac arrest in pediatric patients, including severe comorbidities of the cardiovascular and/or respiratory systems, restrictions on drug administration, increased sensitivity to oxygen desaturation, sensitivity in the airways, difficult airway management, and increased sensitivity to changes in the circulatory and/or respiratory systems.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The finding is consistent with the result from a previous study at our center29 as well as other studies reporting that pediatric patients are at a higher risk for cardiac arrest and higher morbidity in the peri- and postoperative periods in traumatic cases. It was also reported that pediatric patients with high ASA physical status classification suffering from injury before receiving anesthesia had a higher cardiac arrest and comorbidity rate 13,11,18,30. Several factors may explain this increased risk of cardiac arrest in pediatric patients, including severe comorbidities of the cardiovascular and/or respiratory systems, restrictions on drug administration, increased sensitivity to oxygen desaturation, sensitivity in the airways, difficult airway management, and increased sensitivity to changes in the circulatory and/or respiratory systems.…”
Section: Discussionmentioning
confidence: 98%
“…Such cases involve high blood loss prior to hospital arrival, possibly unknown to the surgery and anesthesia teams. Many studies have shown that traumatic cases with high morbidity also involve blood loss 3,18,30. In one study, the highest cardiac arrest rates occurred in cases involving intraoperative transfusion, traumatic cases, poor ASA physical status classification, and emergency surgery 3,6,15.…”
Section: Discussionmentioning
confidence: 99%
“…Survival among infants has been documented between 1.4% and 1.7% . In contrast, overall survival in children of all age groups is generally slightly higher, although varying widely (2.0–12.1%) with median of 8% . In comparison, in‐hospital arrests have a better outcome with 48.5–62% achieving return of spontaneous circulation (ROSC) and 15.4–48.7% surviving to discharge …”
Section: Introductionmentioning
confidence: 99%
“…2,4,5 Previous studies have reported factors that are associated with survival in children with traumatic OHCA, such as hypoxia-caused arrest, prehospital resuscitation course, witness presence, shorter transportation duration, and inhospital resuscitation. 1,2,5,9,10 However, the contribution of medication (ie, epinephrine) for pediatric resuscitation has not been well documented.…”
Section: Introductionmentioning
confidence: 99%